Online Marketing Counseling and Assistance for MSMEs Dakota Convection - Anita Primastiwi; Desy Tri Inayah; Diki Sandi Andrian; Sri Indah Ergina; Indra Pratama; Agung Sulistio (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Sleman Regency is one of the regencies located in the Special Region of Yogyakarta Province, the beauty and natural wealth that is served even attracts the attention of many tourists, both local and international. In addition to the beautiful natural panorama, Sleman Regency also has many MSME actors so that it really supports the completeness of tourism in Sleman Regency, but due to the Covid-19 pandemic that has hit almost all countries, the tourism and MSME sectors have paralyzed so that a new life transition is needed, one of which is change the marketing of MSME products from offline to online. The presence of the community service team at Bachelorwiyata Tamansiswa University aims to foster the spirit of MSME actors by providing online marketing counseling and assistance to MSME actors. This activity consisted of socialization, counseling and training on online marketing which took place on Tuesday, September 15, 2020. In general, most of the employees at Dakota Convection were enthusiastic to further promote online product marketing through the media website, Instagram, Facebook, and various marketplaces. .